Local Government Accountability in Control Environmental Pollution Of Nest Creation Bird Walets in Pinrang District - Ali Rahman; Danil Danil (Legal Standing : Jurnal Ilmu Hukum, 2020)
Accountability in the implementation of local government to the environment in this study emphasizes the control of environmental pollution due to bird nest breeding. Theresults of this study are expected to provide a positive contribution in the developmentof legal science in the environmental sector and can also be a suggestion for structuringregulations in protecting the environment in Pinrang Regency. The form ofaccountability for the Pinrang Regional Government related to environmental pollutioncontrol, explicitly, the regulations regarding the use of swallow nests carried out by thepeople of Pinrang Regency do not have separate rules. This is because there has notbeen any discussion regarding the proposed special arrangements relating to theutilization of the swallow's nest in Pinrang Regency in the form of the Pinrang RegencyRegional Regulation. So that the form of controlling the swallow business follows theform of licensing in terms of trading business licensing. The accountability of localgovernments is hampered, in that it is not implemented in the form of an explicitarrangement regarding the use of swallow's nests, and the entrepreneurs of swallowbirds follow the designation in the area of Pinrang Regency. Thus, the implementationof the swallow bird business must comply with the existing regulations regarding thespatial plan for the Pinrang Regency area